Exergy analysis of a refrigeration compressor - Lee, Staniel Keng Yong. (2010)
An exergy analysis of a refrigeration compressor is presented in this report. The purpose is to identify and investigate the exergy losses on a rotary compressor, namely the rolling piston compressor. The exergy losses are attributed to heat transfers, adiabatic throttling, irreversible fluid mixing and frictions. They are described on a common basis, as exergy destruction rate or irreversibility.